Arsenic Speciation of Edible Shrimp by High-Performance Liquid Chromatography-Inductively Coupled Plasma-Mass Spectrometry (HPLC-ICP-MS): Method Development and Health Assessment. (22nd September 2019) - Wang, Zhipeng; Xu, Jie; Liu, Yanjun; Li, Zhaojie; Xue, Yong; Wang, Yuming; Xue, Changhu
Abstract: This study aimed at developing an accurate method for determining the levels of total arsenic (As) and arsenic species in edible shrimp with the collision/reaction cell (CRC) in the O2 mass-shift mode to remove interferences. The microwave-assisted extraction method demonstrated satisfactory efficiency (86.9%), and As species were separated rapidly within 11 min when the optimized chromatographic conditions were adopted. During the study, the limits of detection, precision, and spike recovery for six arsenic species were in the ranges from 0.010 to 0.028 μg/L, 1.89 to 3.14%, and 96.9 to 103.2%, respectively. The analytical methods were successfully applied to determine the concentrations of total arsenic and As species in eight shrimp samples. The results showed that arsenobetaine was the predominant As species, and inorganic arsenic contents were below 0.5 mg/kg in the shrimp samples analyzed. The health risk assessment indicated that the shrimp samples detected posed no particular risk of As to local consumers.